2010
DOI: 10.1021/jf903128j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Linolenic Acid Content on the Oxidation of Milk Fat

Abstract: Increasing the content of alpha-linolenic acid in milk fat might be desirable to meet consumer concerns about dietary healthfulness. However, the rich content of polyunsaturated fatty acids (PUFAs) will influence the oxidative stability of milk fat. This experiment was carried out to determine the effects of infusion with different amounts of high-linolenic perilla fatty acid (HLPFA) emulsion into the duodenum of dairy cows on milk fatty acid profile and the susceptibility of milk fat to oxidation. In a crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…Timmons et al (2001) found that feeding cows with whole roasted soybeans increased the content of C18:2 and C18:3 in milk fat, which in turn increased the susceptibility to oxidation. Liu et al (2010) found that infusion with high-linolenic perilla fatty acid emulsion enhanced the content of n-3 PUFAs in milk fat but decreased the oxidative stability of milk fat. The position of double bonds in UFA can affect the oxidative stability of milk.…”
Section: Introductionmentioning
confidence: 95%
“…Timmons et al (2001) found that feeding cows with whole roasted soybeans increased the content of C18:2 and C18:3 in milk fat, which in turn increased the susceptibility to oxidation. Liu et al (2010) found that infusion with high-linolenic perilla fatty acid emulsion enhanced the content of n-3 PUFAs in milk fat but decreased the oxidative stability of milk fat. The position of double bonds in UFA can affect the oxidative stability of milk.…”
Section: Introductionmentioning
confidence: 95%
“…A similar situation was observed in a previous study where greater concentrations of C18:1 in milk did not result in a higher concentration of lipid hydroperoxides, but the elevated concentration of PUFA did (Havemose et al, 2006). And in a second study, Liu et al (2010) observed decreased oxidative stability in milk with increased ω-3 PUFA content. In our study, we did not detect any differences in C18:3 content in milk from the three dietary treatments, potentially because C18:3 and C20:0 co-eluted.…”
Section: Peroxide Value and Free Fatty Acid Contentsupporting
confidence: 85%
“…Higher concentrations of unsaturated fatty acids are also characterized by an "oily" flavor (Kolanowski et al, 2007). Increased CLA increases the susceptibility of milk to oxidation (Liu et al, 2010).…”
Section: Feed-related Off-flavors In Milkmentioning
confidence: 99%
“…(2010) also observed decreased oxidative stability in milk with increased n--3 PUFA content in milk (Liu et al, 2010). In our study, we did not detect any differences in C18:3 content in milk from the 3 DDGS diets (0%, 10%, and 25%), and no apparent oxidation was observed either.…”
Section: Chemical Analysissupporting
confidence: 46%